2016
DOI: 10.1016/j.neuropharm.2016.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary adolescent drinking enhances excitation by low levels of alcohol in a subset of dopaminergic neurons in the ventral tegmental area

Abstract: Enhanced dopamine (DA) neurotransmission from the ventral tegmental area (VTA) to the ventral striatum is thought to drive drug self-administration and mediate positive reinforcement. We examined neuronal firing rates in slices of mouse midbrain following adolescent binge-like alcohol drinking and find that prior alcohol experience greatly enhanced the sensitivity to excitation by ethanol itself (10–50 mM) in a subset of ventral midbrain DA neurons located in the medial VTA. This enhanced response after drinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 46 publications
(71 reference statements)
2
22
0
Order By: Relevance
“…A history of alcohol exposure has been shown to be important in the medial VTA. In brain slices obtained from mice given intermittent access to alcohol during adolescence (PD30–60), 10 mM ethanol has been shown to increase the firing rate of DA neurons in the medial VTA 7.7%, whereas no effect was seen in brain slices from alcohol-naïve mice [24]. While 20 mM ethanol has been found to increase the firing rate of VTA DA neurons in the rat, the firing rates of VTA GABA neurons have been found to decrease by 41% at this concentration [25].…”
Section: Ventral Tegmental Area (Vta)mentioning
confidence: 99%
“…A history of alcohol exposure has been shown to be important in the medial VTA. In brain slices obtained from mice given intermittent access to alcohol during adolescence (PD30–60), 10 mM ethanol has been shown to increase the firing rate of DA neurons in the medial VTA 7.7%, whereas no effect was seen in brain slices from alcohol-naïve mice [24]. While 20 mM ethanol has been found to increase the firing rate of VTA DA neurons in the rat, the firing rates of VTA GABA neurons have been found to decrease by 41% at this concentration [25].…”
Section: Ventral Tegmental Area (Vta)mentioning
confidence: 99%
“…WIN increased the basal spontaneous frequency from ~3 to 5 Hz. The spike frequency in VTA DA neurons of male rats is similar to those of mice (~3 Hz) of the same gender at P60 [22] . Voluntary drinking in these adolescent males did not alter spike rates.…”
Section: Vta Da Neuronsmentioning
confidence: 61%
“…Since VTA in rodents and monkeys has no clear borders (Figure 1 and 2) as a nucleus unlike the amygdala, hippocampus and septum, defining DA neurons would be always 'somewhat misleading' by any criteria [22] . Therefore, also previous studies in rats observed heterogeneities in spike properties and when possible have classified them as type 1 or 2 [24] .…”
Section: Vta Da Neuronsmentioning
confidence: 99%
“…Selective activation of α 7 nAchR results in the release of glutamate in the VTA, which, if paired with postsynaptic depolarization, results in long‐term potentiation in VTA DA neurons (Mansvelder and McGehee, ). In mice, adolescent alcohol consumption increases the sensitivity in select VTA DA neurons to become activated by low concentrations of EtOH (Avegno et al., ). Indirect evidence suggests that these hypersensitive DA neurons produced by adolescent EtOH consumption contain α 7 nAchRs and may be the subset of VTA neurons that coexpress DA and glutamate (Avegno et al., ).…”
Section: Discussionmentioning
confidence: 99%